التواصل البصري وارتباطه بالطبيعة في التصميم الداخلي (Journal of the College of Basic Education, 2025)
Visual communication with nature in interior design contributes to creating healthy and comfortable interior environments for users and enriching the design experience. The introduction of natural elements adds aesthetic touches and visual diversity to the interior design. The use of natural colors and shapes creates a warmer and more organic design atmosphere and helps reduce visual stress and improve the psychological health of users. The introduction of natural lighting and natural landscapes creates a calm and comfortable interior environment. Each interior design has its own energy that plays an important role in influencing the person inside the place, as interior design can be used to restore health such as getting rid of psychological crises and gives the ability to communicate with nature and the surrounding environment. In addition, the lack of sufficient knowledge of the energy of the place and its role in interior design and the neglect and neglect of energy and its strong impact on human comfort within the interior design negatively affects the efficiency of users.